4E analysis of a concentrating photovoltaic thermal system (CPVT) with examining the effects of flow regime and concentration ratio. (November 2022) - Shoaei, Mersad; Moosavian, Seyed Farhan; Hajinezhad, Ahmad
Abstract: Due primarily to environmental concerns, attention to renewable energy sources has increased significantly in recent years. Of these sources, solar energy and wind energy have received the most study. With the improvement in photovoltaic (PV) panels' efficiency, photovoltaic (PV) panels have grown significantly in popularity among the various solar energy methods. One hybrid system that uses these panels is the concentrating photovoltaic thermal (CPVT) system. Throughout the present study, an analysis of energy, exergy, environmental, and economic (4E analysis) aspects have been conducted. In addition, the life cycle assessment (LCA) method has been used to evaluate the system's performance. Moreover, the effects of the working fluid flow type regime and the concentration ratio (CR) have been evaluated. The results indicate that CPVT will have about 63% of the total energy efficiency and 9% of the total exergy efficiency. CO2 emissions for the system could cost as much as 20 cents a year in a worst-case scenario.